أسلوب التعليل في سورة البقرة (دراسة نحوية تحليلية) - Abdul Wahab Naf'an (IAIN Salatiga, 2018)
This study aims to exploratory and analytical study expressions to explain the reasons or causes of something (at-ta'lîl) in the Qur'an of surah al-Baqarah. The approach used is inductive (istiqra'iy), which is the conclusion or the theory formulation (kaedah) taken after the research of all or some elements. The results of this study reveal that there are two ta'lils, which are with letters and with ism. Letter lâm is the master letter in revealing the most reasons or causes in the surah al-Baqarah which is then followed thereafter by the letters bâ`, in sababiyah, hattâ, min, 'an, fî, inna,' alâ and idz. While in the form of ism, it shapes as maf'ul liajlih.